Pendampingan Tenaga Kependidikan dalam Penyusunan Administrasi Sarana Prasarana di Lembaga Pendidikan Islam - Danang Dwi Prasetyo (MUJAHADA: Jurnal Pengabdian Masyarakat, 2023)
This Community Service aims to explore administrative management at the Bina Anak Sholeh Foundation Educational Institution Yogyakarta. Assistance in the preparation of data on infrastructure facilities needed by schools is assisted by Microsoft Exel 2013 Software so that the work process runs effectively and efficiently because it contains tools that can be used.